2003
DOI: 10.1046/j.1529-8817.2003.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

REVERSAL OF HELIX ORIENTATION IN THE CYANOBACTERIUM ARTHROSPIRA1

Abstract: A survey of the morphological characters of 36 clonal axenic strains of Arthrospira showed that 34 had helical and 2 had straight trichomes. Of those with helical trichomes, five were right‐handed and 29 left‐handed. After repeated subculture for 1 year, the orientation of one helical strain (D893) had changed from right‐ to left‐handed, suggesting a probable genetic shift. The influence of environmental factors on helix orientation was tested on a subset of 10 strains. A temperature upshift from 30 to 32–34° … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 28 publications
0
56
0
3
Order By: Relevance
“…An unusual but similar phenomenon is exhibited by the cyanobacterium Arthrospira, which grows as helical trichomes, i.e., long filaments of individual cells encased and aligned within a common tubular structure (224). When exposed to protistan grazing, two helical Arthrospira trichomes began the experiment growing as right-handed spiral trichomes.…”
Section: Selection For Altered Shapementioning
confidence: 93%
See 2 more Smart Citations
“…An unusual but similar phenomenon is exhibited by the cyanobacterium Arthrospira, which grows as helical trichomes, i.e., long filaments of individual cells encased and aligned within a common tubular structure (224). When exposed to protistan grazing, two helical Arthrospira trichomes began the experiment growing as right-handed spiral trichomes.…”
Section: Selection For Altered Shapementioning
confidence: 93%
“…When exposed to protistan grazing, two helical Arthrospira trichomes began the experiment growing as right-handed spiral trichomes. However, at the end of the experiments these had changed so that left-handed spiral filaments dominated (224). In fact, while grazing, the ciliate predator rotates to follow the Arthrospira spiral during feeding (224) and turns on its axis while sucking in up to six complete bacterial coils (A. Belay, personal communication).…”
Section: Selection For Altered Shapementioning
confidence: 99%
See 1 more Smart Citation
“…can alter according to environmental changes. Mühling et al (2003) found that the helix orientation could be reversed by temperature changes. Wang and Zhao (2005) proved that the morphogenesis of Arthrospira filaments from spiral to linear was due to DNA mutation.…”
Section: Discussionmentioning
confidence: 98%
“…Destacam-se principalmente pela natureza dos pigmentos fotossintéticos -a clorofila "a" e as ficobiliproteínas, e pela estrutura e composição química da parede celular, As espécies do gênero Arthrospira são formadas principalmente por tricomascadeias de células cilíndricas dispostas em forma helicoidal, que variam de tamanho e morfologia conforme as condições de crescimento (CIFERRI, 1983;TIBONI, 1985). A orientação desses tricomas, por exemplo, pode ser afetada pela temperatura a qual as células são submetidas, ou por qualquer tipo de estresse mecânico, como a agitação contínua durante um cultivo (MÜHLING et al, 2003 As espécies do gênero Arthrospira ocorrem naturalmente no solo, na areia, nas marismas, em água doce, em água salobra e em água do mar (CIFERRI, 1983;TIBONI, 1985). São tipicamente encontradas em alguns lagos alcalinos e salinos do México e da África, especialmente na região africana de Chad (ABDULQADER; BARSANTI; TREDICI, 2000), onde crescem naturalmente junto a outras cianobactérias em lagos com concentração salina inferior a 30 g L -1 e com pH entre 7,0 e 9,5 (CIFERRI, 1983;TIBONI, 1985).…”
Section: Cianobactérias Do Gênero Arthrospira (Spirulina)unclassified